LITERATURE REVIEW: Hubungan Dynamic Balance Terhadap Risiko Terjadinya Cedera Pada Pemain Sepak Bola - Nabilla Fitria Emily (2020)
Objective: Dynamic balance has been little investigated or scrutinized in football, especially in the case of elite players and more importantly, it is currently unknown whether there is a relationship between static and dynamic balance abilities. The writing of this scientific work was carried out with the aim, to find out the relationship of balance to the risk of injury to soccer players and to understand FIFA 11+ training relationships on dynamic equilibrium for soccer players. Method: The method used in this research is using the literature review method. The data source in this research is to use several databases such as Google Scholar, PubMed, Science Direct. From the literature search results there are 3 articles and journals that meet the inclusion criteria. The source of the assessment methodology is 3 articles with Scimago Journal & Country Rank (SJR) and journal analysis using the appropriateness of research methods, topics used, parameters, and the results of each article. Results: After a review of the literature with 3 articles shows that dynamic balance can reduce the risk of injury to soccer players. Conclusion: There is a dynamic balance relationship between the occurrence of injury to a significant soccer player.